Transcriptional Repression by the Retinoblastoma Protein through the Recruitment of a Histone Methyltransferase - Vandel, Laurence (American Society for Microbiology, 2001)
The E2F transcription factor controls the cell cycle-dependent expression of many S-phase-specific genes. Transcriptional repression of these genes in G(0) and at the beginning of G(1) by the retinoblasma protein Rb is crucial for the proper control of cell proliferation. Rb has been proposed to function, at least in part, through the recruitment of histone deacetylases. However, recent results indicate that other chromatin-modifying enzymes are likely to be involved. Here, we show that Rb also interacts with a histone methyltransferase, which specifically methylates K9 of histone H3. The results of coimmunoprecipitation experiments of endogenous or transfected proteins indicate that this histone methyltransferase is the recently described heterochromatin-associated protein Suv39H1. Interestingly, phosphorylation of Rb in vitro as well as in vivo abolished the Rb-Suv39H1 interaction. We also found that Suv39H1 and Rb cooperate to repress E2F activity and that Suv39H1 could be recruited to E2F1 through its interaction with Rb. Taken together, these data indicate that Suv39H1 is involved in transcriptional repression by Rb and suggest an unexpected link between E2F regulation and heterochromatin.